PP.32.19: MAGNETIC RESONANCE IMAGING OF ADRENAL GLANDS IN PATIENTS WITH MODERATE ARTERIAL HYPERTENSION. (June 2015) - Belichenko, O.; Vorontsov, V.; Averkieva, E.; Vladimirova, V.; Babaeva, A.
Abstract : Objective: To evaluate MRI diagnostic possibilities of adrenal glands in patients with moderate arterial hypertension (AH). Design and method: MRI of adrenal glands was performed in group of 150 patients (65 male, 85 female aged from 35 to 55 y.o) with moderate AH, and in control group of 28 persons of the same age without AH. All people examined did not have diagnosed endocrine disorders. All patients with AH recieved hypotensive treatment. Standard MRI of adrenals included regular T1-, T2-weighted, and fat saturation T1-, T2-weighted sequences. Results: Our study included 150 patients with moderate AH and 25 healthy persons. In 21 patients with we found inhomogenity and unilateral thickening of adrenals from 6 to 9 mm. In 11 patients small (4–8 mm) unilateral nodular structures were determined. In 7 patients with we found bilateral thickening of adrenals. In 5 patients bilateral nodular structures of different sizes were determined. In healthy persons we found bilateral thickening of adrenals in 3 cases (12%) and no nodular changes were detected. Thus, enlargement of adrenals without nodular changes were found in 28 pts (19%) patients, nodular hyperplasia was determined in 16 pts (11%). Dynamic examination after 2–3 years was performed in 41 patients and found no considerable changes of adrenals. Conclusions: MRI is a high effective method of adrenal glands evaluation in patients with moderate AH. Diffuse enlargement and nodular changes of adrenals are more often found in patients with moderate AH than in healthy persons. Dynamic examination in most patients with changes in adrenal glands and moderate AH is not necessary.